Ethnic differences between South Asians and white Caucasians in cardiovascular disease-related mortality in developed countries: a systematic literature review protocol - Olalekan Abdulrahman Uthman; Mubarak Patel; Salim Abatcha (BMJ Open)
Introduction Cardiovascular disease (CVD) is the leading cause of death worldwide, with significantly worse CVD outcomes in ethnic minorities in developed countries, especially South Asians, compared with the prevailing white ethnic group. This protocol outlines the process for conducting a systematic literature review to investigate the CVD outcome inequalities between South Asian and white Caucasian ethnic groups.Methods Studies that compared the South Asian ethnic minority with the predominant white ethnicity in developed countries with CVD will be included from inception to 22 April 2021. We will search MEDLINE, Embase, Web of Science and grey literature to find all relevant peer-reviewed articles, reports and online theses. Articles will be screened using inclusion/exclusion criteria applied first at the title and abstract level, and then full texts, both by two independent reviewers. Articles kept in the review will undergo a risk of bias assessment using the Quality In Prognosis Studies tool and data will be extracted. Random-effects meta-analysis and heterogeneity tests will be undertaken, and tests for publication bias, outlying highly-influential observations. If insufficient data is founded or studies are highly heterogeneous, a narrative synthesis will be conducted.Ethics Formal ethical approval is not required for this review.Dissemination The results and findings of this systematic literature review will be disseminated through peer-reviewed publications and reports.PROSPERO registration number CRD42021240865.